ChemInform Abstract: Synthesis of Aza and Carbocyclic β‐Carbolines for the Treatment of Alcohol Abuse. Regiospecific Solution to the Problem of 3, 6‐Disubstituted β‐ and Aza‐β‐carboline Specificity. Issue 10 (February 2016) - Phani Babu Tiruveedhula, V. V. N.; Methuku, Kashi Reddy; Deschamps, Jeffrey R.; Cook, James M.
Abstract: An improved method is elaborated for the synthesis of azacarbolines (IV) and carbolines (VII) by a Buchwald—Hartwig amination followed by an intramolecular Heck‐type cyclization.